COMPARATIVE pH ANALYSIS: HOMEMADE COLD CLAY VERSUS COMMERCIAL CLAY FOR CHILD SAFETY - Centaury Harjani; Dwi Aditiyarini; Vinsa Cantya Prakasita (BRIN - Badan Riset dan Inovasi Nasional, 2025)
Cold clay, as a non-baking children's play medium, needs to be assessed for its chemical and physical safety, particularly its pH parameters, to ensure safety for children's skin and environmental sustainability. This study aims to characterize the pH of cold clay by comparing homemade and manufactured products. A total of six samples were tested: one homemade (based on polyvinyl acetate, cornstarch, and additives) and five manufactured, colorful ones. The pH measurements were performed using a digital pH meter with three replications, then statistically analyzed using an independent t-test. The results showed a highly significant difference (p < 0.001) between the two groups. Homemade samples had an average pH of 4.75 ± 0.06 (acidic), while manufactured samples ranged from 7.16–7.53 (neutral to slightly alkaline). From a dermatological perspective, homemade pH, which is closer to the natural pH of children's skin ( 5.5), is considered safer for long-term contact because it does not disrupt the acid mantle. In contrast, the neutral pH of manufactured products showed better chemical stability but potentially poses challenges in waste management. These findings emphasize the importance of pH characterization in selecting safe materials for the intended application. The study recommends consideration of pH parameters for parents, educators, and industry, as well as the need for further studies on toxicity and environmental impacts to ensure overall safety.